2008
DOI: 10.1098/rstb.2008.0216
|View full text |Cite
|
Sign up to set email alerts
|

Defining disruptive coloration and distinguishing its functions

Abstract: Disruptive coloration breaks up the shape and destroys the outline of an object, hindering detection. The principle was first suggested approximately a century ago, but, although research has significantly increased, the field remains conceptually unstructured and no unambiguous definition exists. This has resulted in variable use of the term, making it difficult to formulate testable hypotheses that are comparable between studies, slowing down advancement in this field. Related to this, a range of studies do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
242
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(249 citation statements)
references
References 39 publications
6
242
0
1
Order By: Relevance
“…This immediately suggests that the coloured scales in the concave pits serve to camouflage the weevil against a mainly green background (see also figure 1a), especially for their common predators, birds [40]. Further, the dotted arrangement of the pits on the elytra will support camouflage by disruptive patterning, a common mechanism to achieve camouflage [8], e.g. applied by cuttlefish [7,41].…”
Section: Discussion (A) Biophotonic Structures In Weevils and Beetlesmentioning
confidence: 99%
“…This immediately suggests that the coloured scales in the concave pits serve to camouflage the weevil against a mainly green background (see also figure 1a), especially for their common predators, birds [40]. Further, the dotted arrangement of the pits on the elytra will support camouflage by disruptive patterning, a common mechanism to achieve camouflage [8], e.g. applied by cuttlefish [7,41].…”
Section: Discussion (A) Biophotonic Structures In Weevils and Beetlesmentioning
confidence: 99%
“…An inducible morphological defence can increase a prey's chance of escaping an attack [19]; in this case, pigmentation linked to camouflage may decrease predation rate by reducing encounter rates with predators [10]. Furthermore, pigmentation can improve crypsis owing to, for example, background matching [8,9] or disruptive coloration in which prey try to break the outline of the body [20]. We showed that snails exposed to predatory fish increased the amount of pigmentation without affecting the pattern complexity.…”
Section: Discussionmentioning
confidence: 90%
“…Disruptive coloration creates the appearance of false edges and also destroys the appearance of the true body edges and outline, which hinders the ability of a predator to detect or recognize an animal by its shape (Thayer 1909; Cott 1940; Stevens and Merilaita 2009b, 2011; Webster et al. 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2005, 2006; Merilaita and Lind 2005; Fraser et al. 2007) is the “disruptive marginal pattern,” in which the disruptive markings touch the outline of the prey's body (Cott 1940; Stevens and Merilaita 2009b). Disruptive marginal patterns are effective even when some of the pattern elements do not visually match adjacent parts of the background (Cuthill et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation